De novo variants in TCF7L2 are associated with a syndromic neurodevelopmental disorder. Issue 8 (18th May 2021) - Dias, Caroline; Pfundt, Rolph; Kleefstra, Tjitske; Shuurs‐Hoeijmakers, Janneke; Boon, Elles M. J.; van Hagen, Johanna M.; Zwijnenburg, Petra; Weiss, Marjan M.; Keren, Boris; Mignot, Cyril; Isapof, Arnaud; Weiss, Karin; et al.
Abstract: TCF7L2 encodes transcription factor 7‐like 2 (OMIM 602228), a key mediator of the evolutionary conserved canonical Wnt signaling pathway. Although several large‐scale sequencing studies have implicated TCF7L2 in intellectual disability and autism, both the genetic mechanism and clinical phenotype have remained incompletely characterized. We present here a comprehensive genetic and phenotypic description of 11 individuals who have been identified to carry de novo variants in TCF7L2, both truncating and missense. Missense variation is clustered in or near a high mobility group box domain, involving this region in these variants' pathogenicity. All affected individuals present with developmental delays in childhood, but most ultimately achieved normal intelligence or had only mild intellectual disability. Myopia was present in approximately half of the individuals, and some individuals also possessed dysmorphic craniofacial features, orthopedic abnormalities, or neuropsychiatric comorbidities including autism and attention‐deficit/hyperactivity disorder (ADHD). We thus present an initial clinical and genotypic spectrum associated with variation in TCF7L2, which will be important in informing both medical management and future research.